How Situational Context Impacts Empathic Responses and Brain Activation Patterns - Cheng, Yawei; Chen, Chenyi; Decety, Jean (Frontiers in Behavioral Neuroscience, 2017)
Clinical empathy, which is defined as the ability to understand the patient’s experience and feelings from the patient’s perspective, is acknowledged to be an important aspect of quality healthcare. However, how work experience modulates the empathic responses and brain activation patterns in medical professions remains elusive. This fMRI study recruited one hundred female nurses, who varied the length of work experience, and examined how their neural response, functional connectivity, and subjective evaluations of valence and arousal to perceiving another individual in physical pain are modulated by the situational context in which they occur (i.e., in a hospital or at home). Participants with longer hospital terms evaluated pain as less negative in valence and arousal when occurring in a hospital context, but not in a home context. Physical pain perceived in a hospital compared to a home context produced stronger activity in the right temporoparietal junction (rTPJ). The reverse comparison resulted in an increased activity in the insula and anterior midcingulate cortex (aMCC). Mediation analysis indicated that reduced personal accomplishment, a symptom of burnout, breaks down the mediation effect of the putamen on context-dependent valence ratings. Overall, the study demonstrates how situational contexts significantly influence individuals’ empathic processing, and that perceiving reward from patient care protects them from burnout. Highlights - Differences in behavior ratings and brain activations between medical practitioners perceiving others’ pain in a hospital and at home. - Situational contexts significantly influence individual’s empathic processing. - Perceiving rewards from patient care protects medical practitioners from burnout. - Empathy is a flexible phenomenon.